The association between higher body mass index and poor school performance in high school students. Issue 6 (21st October 2015) - Tonetti, L.; Fabbri, M.; Filardi, M.; Martoni, M.; Natale, V.
Summary: Background/objective: This study aimed to examine the association between body mass index (BMI) and school performance in high school students by controlling for relevant mediators such as sleep quality, sleep duration and socioeconomic status. Methods: Thirty‐seven high school students (mean age: 18.16 ± 0.44 years) attending the same school type, i.e. 'liceo scientifico' (science‐based high school), were enrolled. Students' self‐reported weight and height were used to calculate BMI. Participants wore an actigraph to objectively assess the quality and duration of sleep. School performance was assessed through the actual grade obtained at the final school‐leaving exam, in which higher grades indicate higher performance. Results: BMI, get‐up time, mean motor activity, wake after sleep onset and number of awakenings were negatively correlated with the grade, while sleep efficiency was positively correlated. When performing a multiple regression analysis, BMI proved the only significant (negative) predictor of grade. Conclusions: When controlling for sleep quality, sleep duration and socioeconomic status, a higher BMI is associated with a poorer school performance in high school students.